Overexpressing miR-122-5p Inhibits the Relaxation of Vaginal Smooth Muscle in Female Sexual Arousal Disorder by Targeting Vasoactive Intestinal Peptide Receptor 1 - Cong, Shengnan; Gui, Tao; Shi, Qinchuan; Zhang, Jingjing; Feng, Jingyi; Pan, Lianjun; Ma, Jiehua; Zhang, Aixia (Sexual medicine, 2021)
Female sexual arousal disorder (FSAD) is a common issue causing physical and psychological pain, but it has no standard diagnostic criteria or treatment. So its pathogenesis desiderates to be explored. To investigate the specific function of miR-122-5p in FSAD. 18 subjects were grouped into FSAD and normal control groups according to the Chinese version of the Female Sexual Function Index, and the expression levels of miR-122-5p and vasoactive intestinal peptide receptor 1 (VIPR1) protein in their tissue were verified through real-time quantitative polymerase chain reaction (qRT-PCR) and western blot (WB) analysis. Then in vitro experiment, miR-122-5p was overexpressed or inhibited in rat vaginal smooth muscle cells (SMCs). The relaxation of rat vaginal SMCs was reflected by the cell morphology, intracellular free cytosolic calcium ion (Ca2+) levels, cell proliferation and apoptosis, together with the cyclic adenosine monophosphate (cAMP) concentration and protein kinase A (PKA) activities. Additionally, the expression levels of relaxation-related proteins, including VIPR1, stimulatory G protein (Gs), adenylate cyclase (AC), and PKA, were detected based on WB analysis. Furthermore, a rescue experiment that simultaneously overexpressed or silenced miR-122-5p and VIPR1 was conducted, and all the indicators were evaluated. The expression level of VIPR1 and downstream proteins, cell morphology, cell proliferation and apoptosis, and intracellular free Ca2+ levels were examined. We verified that women with FSAD had higher miR-122-5p and lower VIPR1 protein. Then overexpressing miR-122-5p decreased relaxation of rat vaginal SMCs, which was manifested as a contractile morphology of cells, an increased intracellular free Ca2+ concentration, and lower cAMP concentration and PKA activity. Moreover, by rescue experiments, we inferred that VIPR1 was the target of miR-122-5p and affected the relaxation function of vaginal SMCs. miR-122-5p regulates the relaxation of vaginal SMCs in FSAD by targeting VIPR1, ulteriorly providing an underlying diagnostic and therapeutic target for FSAD. Cong S, Gui T, Shi Q, et al. Overexpressing miR-122-5p Inhibits the Relaxation of Vaginal Smooth Muscle in Female Sexual Arousal Disorder by Targeting Vasoactive Intestinal Peptide Receptor 1. Sex Med 2021;9:100390.